Correlation of serum free prostate-specific antigen level with histological findings in patients with prostatic disease - Lakhey, M; Ghimire, R; Shrestha, R; Bhatta, AD (Kathmandu University Medical Journal, 2010)
Background: Prostate Specifi c Antigen (PSA) has been widely used in the diagnosis and management of patients with prostate cancer. It may be elevated in other prostatic diseases and surgical procedures. PSA exists in two forms, a major bound form (cPSA) and a free form (fPSA). Objectives: The objective of the study was to determine the relationship between serum fPSA levels and histologic findings in biopsy specimens of men with prostatic disease. Material and methods: This study includes 91 patients planned for transurethral resection of prostate (TURP). Blood samples were collected before TURP and tested for fPSA. Histology of the tissue samples collected after TURP were studied and the relationship with fPSA analysed using SPSS 11.5. Results: The median values for benign, premalignant and malignant lesions were 1.8ng/ml, 4.5ng/ml and 13.20ng/ml respectively (p<0.001). Most cases of benign prostatic hyperplasia(BPH) without inflammation had fPSA levels <2ng/ ml, while most with active inflammation had levels >5ng/ml. Low grade prostatic intraepithelial neoplasia (LGPIN) saw levels <5ng/ml while high grade intraepithelial neoplasia (HGPIN) and prostate cancer (PCa) had levels > 5ng/mL (p<0.05). For detection of high grade lesions (HGPIN and PCa), the sensitivity and specificity of fPSA level > 5ng/ml was found to be 88.8% and 90.2% respectively. Conclusions: Serum fPSA is elevated marginally in patients with BPH without inflammation. Active inflammation and high grade lesions are associated with fPSA level more than 5 ng/ml. Key words: Benign prostatic hyperplasia; fPSA; prostate cancer; prostatic intraepithelial neoplasia. DOI: 10.3126/kumj.v8i2.3550 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 158-163